Underage drinking on saturday nights, sociodemographic and environmental risk factors: a cross-sectional study - Galasso Laura; Tognazzo Federica; Forza Giovanni; Buja Alessandra; Chindamo Sonia; Gallimberti Luigi; Vinelli Angela; Baldo Vincenzo (BMC, 2011)
Abstract Background Excessive alcohol consumption in underage people is a rising phenomenon. A major proportion of the disease burden and deaths of young people in developed nations is attributable to alcohol abuse. The aim of this study was to investigate social, demographic and environmental factors that may raise the risk of Saturday night drinking and binge drinking among Italian school students. Methods The study was conducted on a sample of 845 Italian underage school students, by means of an anonymous, self-test questionnaire. Multivariate logistic regression was applied to identify independent risk factors for alcohol drinking and binge drinking. Ordered logistic regression was used to identify independent risk factors for harmful drinking patterns. Results The independent variables that confer a higher risk of drinking in underage students are older age classes, male sex, returning home after midnight, belonging to a group with little respect for the rules, or to a group where young people are not seen as leaders. The higher the perception of alcohol consumption by the group, the higher the risk. Spending time in bars or discos coincides with a two-fold or four-fold increase, respectively, in the risk of alcohol consumption. Conclusion Our findings show that certain environmental and social risk factors are associated with underage drinking. The most important role for preventing young people's exposure to these factors lies with the family, because only parents can exert the necessary control and provide a barrier against potentially harmful situations.